COMPETENCIES FOR FORM SIX GEOGRAPHY TEACHERS IN REACHING THE MALAYSIAN EDUCATION QUALITY STANDARDS - Hanifah, Mahat; Mohmadisa, Hashim; Yazid, Saleh; Nasir, Nayan; Saiyidatina Balkhis, Norkhaidi (Jurnal Cakrawala Pendidikan, 2019)
We conducted this study to evaluate the competencies of Form Six geography teachers in achieving the Malaysian Education Quality Standards. We applied a qualitative approach using the observation technique. The respondent observation consisted of three teachers who had more than 10 years of experience teaching Form Six geography and who were working in the areas of Batang Padang district, Perak and Hulu Selangor district, Malaysia. The variables we assessed were practical knowledge, subject-content knowledge, pedagogical content knowledge, pedagogical technology knowledge, teachers' teaching of professional behaviours and attitudes, and values modified from the Quality Level Rubric of the Malaysian Education Quality Standards. The observation findings showed that each teacher scored different points, ranging from three to four for the assessed variables. Teachers' pedagogical technology knowledge needs to be improved as two out of three teachers were still using Teaching Aid Materials such as mahjong paper and marker rather than using computer or other more recent technology due to the lack of infrastructure provided by their schools. In conclusion, Form Six geography teachers in this study have fulfilled the competence of the Malaysian Education Quality Standards by achieving the maximum score.